DESIGN OF PEDAGOGICAL MOBILE ANCIENT HUMAN SETTLEMENT LEARNING FOR SUPPORTING GEO-HISTORY COMPREHENSION, 21ST CENTURY SKILL THROUGH GOOGLE EARTH APPLICATION - Chitphon Yachulawetkunakorn; Witsanu Supandee; Ratthakarn Na Phatthalung (PEOPLE: International Journal of Social Sciences, 2025)
The advancements in educational technology has developed rapidly over the decade. The convenience to access information from online databases has prompted schools worldwide to start incorporating certain technologies into teaching and learning practices as deemed appropriate. In this research, the Google Earth application was utilized to design learning experiences for Grade 10th students to enhance their comprehension of Geography and History including the 21st century skill, which was achieved from Khok Phanom Di Archaeological site fieldtrip, and assessing learning outcomes by creating the ancient human settlement through the Google Earth application. According to the learning achievement, and the self-assessment of the 21st century skill founded that most of learners could develop the essential skill and gain a deeper comprehension in term of academic comprehension after exploring the PMAG field trip significantly, the statistic significant findings (p<0.05). In addition, most of learners could accurately create the ancient maps according to geographical principles, plate tectonics theory, it can be concluded that the pedagogical mobile ancient human settlement learning through Google Earth could support the acquisition of Geography and History knowledge effectively.